SUBSTITUTION ON THE FAMOUS INDONESIAN NOVEL “AYAT AYAT CINTA” WRITTEN BY HABIBURRAHMAN SAEROZI - Chalimah Chalimah; Sumarlam Sumarlam (Universitas Pendidikan Mandalika, 2017)
After being explained about substitution by one of my lecturers, professor Sumarlam, I am interested in investigating the substitution on a famous novel. I choose “Ayat Ayat Cinta” a novel written by Habiburrahman Saerozi. It is very famous in Indonesia and it is not only interesting to read but also it gives us education and the way to love someone seen from Moslem side. There are so many some moral values given there. The novel tells us about true love, honesty, pride, and struggle. The data which I analyzed was only in the sub title “Gadis Mesir Itu Bernama Maria”. The aim of this study is to describe the substitution used by the great writer. I am definitely sure that it will give good contribution on understanding about substitution. The ground theory which I use is from (Sudaryanto, 1993:15). He stated that there were four kinds of substitution, such as: equal quality substitution, definite readdressing substitution, nominal predicative substitution, pronominal substitution. I analyzed the data by describing the substitution used based on substitution theory. There are four findings which I can get after investigating the substitution used in the novel, namely: 1) there is no nominal predicative substitutions but the pronominal substitution is mostly used, 2) one word can substitute two words, 3) the writer differs the calling between friends and teachers to show respect, 4) aku (I) as subject sometimes are not fully written in Indonesian.